Synergistic Effects of Combined Nurr1 Overexpression and Natural Inducers on the More Efficient Production of Dopaminergic Neuron-Like Cells From Stem Cells - Beiki, Reyhaneh; Khaghani, Mahsa; Esmaeili, Fariba; Dehghanian, Fariba (Frontiers in Cellular Neuroscience, 2022)
The development of dopaminergic (DA) neurons is a very complex process, and a combination of extrinsic and intrinsic factors involves their differentiation. Transcription factor, Nurr1 (NR4A2) plays an essential role in the differentiation and maintenance of midbrain DA neurons. Nurr1-based therapies may restore DA function in Parkinson's disease (PD) by replacing damaged cells with differentiated cells derived from stem cell. Providing tissue-specific microenvironments such as brain extract can effectively induce dopaminergic gene expression in stem cells. The present study aimed to investigate the combined effects of Nurr1 gene overexpression and a neonatal rat brain extract (NRBE) induction on dopaminergic differentiation of P19 stem cells. In order to neural differentiation induction, stably Nurr1-transfected cells were treated with 100 µg/ml of NRBE. The differentiation potential of the cells was then evaluated during a period of one to three weeks via various methods. The initial evaluation of the cells by direct observation under a light microscope and cresyl violet specific staining, confirmed neuron-like morphology in the differentiated cells. In addition, different molecular and cellular techniques, including real-time PCR, immunofluorescence, and flow cytometry, demonstrated that the treated cells expressed pan-neuronal and dopaminergic markers. In all experimental groups, neuronal phenotype with dopaminergic characteristics mainly appeared in the second week of the differentiation protocol. Overall, the results of the present study revealed for the first time the synergistic effects of Nurr1 gene overexpression and possible soluble factors that existed in NRBE on the differentiation of P19 stem cells into dopaminergic cells.